Assessing the economics and finances of Artisanal and small-scale gold mining in Guyana. (January 2023) - Laing, Timothy; Edwards, René; Yusuf, Shereeda; Sparman, Colin
Abstract: Artisanal and small-scale mining (ASM) is a vital source of non-farm rural income across much of the Global South, and a key provider of jobs and livelihoods in South America, Africa and Asia. Despite this importance, however, there is very little research into the economics and finances of these small (and often medium-sized) operations. This paper summarises the result of a survey of ASM gold miners in Guyana in late 2020 that delved into the costs, revenues, financing and profitability of a range of small and medium-size miners in the country, for which the industry is a vital source of foreign exchange, economic growth and employment. The results from the survey highlight a potentially lucrative sector with some operators making large profits. However average figures mask a long-tailed distribution with many miners operating at the margins of profitability or a loss. These challenges are amplified by the large capital costs associated with operating in the sector, which are compounded by the difficulties miners face accessing capital markets. Beyond the headline figures, the survey highlights the potential attractiveness of the sector in terms of wages, and also the very small share of costs relating to the use of mercury – highlighting the challenge of utilising economic policy to reduce and eliminate the use of the chemical. The results demonstrate the need to collect more economic and financial data on the sector in order to best understand how to drive change in the sector, helping to mitigate its negative social and environmental impacts, whilst maximising the economic benefits it can bring. Highlights: Small and medium scale mining is a major industry in Guyana. Study undertakes an economic and financial analysis of the sector. Finds a sector that is both potentially highly profitable and also operating on the margin. Capital costs are critical. Costs of mercury are very small – making economic policy to reduce its use challenging.